2021
DOI: 10.3389/fendo.2021.702138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cardiometabolic Factors on the Association Between Serum Uric Acid and Chronic Kidney Disease in Chinese Middle-Aged and Older Population: A Mediation Analysis

Abstract: IntroductionTo explore whether dyslipidemia, hyperglycemia or hypertension has mediating effect on the association between serum uric acid (SUA) and the development of chronic kidney disease (CKD).MethodsWe conducted a mediation analysis to explore the potential mediating effects of systolic blood pressure (SBP), diastolic blood pressure (DBP), blood glucose, triglyceride (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) on the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…However, its use within the cardiovascular sphere has been progressively expanding in recent years. 36 , 37 The results show that the mediating effect of FIB-4 mediated by NLR on coronary heart disease was significant, and the direct effect was not significant, which means that within the early-stage NAFLD population, liver fibrosis might primarily spur atherosclerosis progression through the conduit of inflammation. In contrast, Chen et al’s 20 mediation analysis indicated both mediating and direct effects concerning the association between NAFLD fibrosis markers and the coronary Gensini score.…”
Section: Discussionmentioning
confidence: 90%
“…However, its use within the cardiovascular sphere has been progressively expanding in recent years. 36 , 37 The results show that the mediating effect of FIB-4 mediated by NLR on coronary heart disease was significant, and the direct effect was not significant, which means that within the early-stage NAFLD population, liver fibrosis might primarily spur atherosclerosis progression through the conduit of inflammation. In contrast, Chen et al’s 20 mediation analysis indicated both mediating and direct effects concerning the association between NAFLD fibrosis markers and the coronary Gensini score.…”
Section: Discussionmentioning
confidence: 90%
“…Our analysis did not account for RAS inhibitor and CCB usage, yet it revealed a substantial risk of CKD with concurrent high sUA and hypertension. Despite this correlation, mediation analysis suggested hypertension may not serve as a mediating factor in sUA-induced CKD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%